Farnesoid X Receptor Activation in Brain Alters Brown Adipose Tissue Function via the Sympathetic System - Deckmyn, Benjamin; Domenger, Dorothée; Blondel, Chloé; Ducastel, Sarah; Nicolas, Emilie; Dorchies, Emilie; Caron, Emilie; Charton, Julie; Vallez, Emmanuelle; Deprez, Benoit; Annicotte, Jean-Sébastien; Lestavel, Sophie; et al. (Frontiers in Molecular Neuroscience, 2022)
The nuclear bile acid (BA) receptor farnesoid X receptor (FXR) is a major regulator of metabolic/energy homeostasis in peripheral organs. Indeed, enterohepatic-expressed FXR controls metabolic processes (BA, glucose and lipid metabolism, fat mass, body weight). The central nervous system (CNS) regulates energy homeostasis in close interaction with peripheral organs. While FXR has been reported to be expressed in the brain, its function has not been studied so far. We studied the role of FXR in brain control of energy homeostasis by treating wild-type and FXR-deficient mice by intracerebroventricular (ICV) injection with the reference FXR agonist GW4064. Here we show that pharmacological activation of brain FXR modifies energy homeostasis by affecting brown adipose tissue (BAT) function. Brain FXR activation decreases the rate-limiting enzyme in catecholamine synthesis, tyrosine hydroxylase (TH), and consequently the sympathetic tone. FXR activation acts by inhibiting hypothalamic PKA-CREB induction of TH expression. These findings identify a function of brain FXR in the control of energy homeostasis and shed new light on the complex control of energy homeostasis by BA through FXR.